Sex Changes and Gonad Maturity of Rivulated Parrotfish Scarus rivulatus (Valenciennes, 1840) from Seribu Islands, Indonesia - Asri Yanti; Sulistiono Sulistiono; Ali Mashar; Sonja Kleinertz (Marine Science Department Diponegoro University, 2023)
Parrotfish (Scarus rivulatus) is a species that can undergo sex change at a certain age and size (hermaphrodite protogynous). This study aims to analyze the process of sex change based on body color and gonadal tissue changes, as well as the gonadal development of the fish. Sampling was conducted monthly from January to September 2022. Fish samples were collected from fishermen in Seribu Islands. The parameters observed were sex, gonad maturity stage, body color changes, and anatomy and histology of the gonad. The samples were 1605 individuals, consisted of 831 females, 309 primary males (initial phase of males), and 465 secondary males (terminal phase of males). The total length of these fish ranged 8.8- 22.4 cm (females), 10.5-22.6 cm (primary males of males), and 15.1-28.1 cm (secondary males). Morphological differences between female fish, primary males, and secondary males are generally showed in body size, fin size, and body coloration. The histological analysis results of the gonads of primary male fish was indicated by the presence of residual perinucleolar oocytes in the layer of the gonads that coexist with sperm tissue. The body size of first mature gonads was 13.0 cm (female), 16.6 cm (primary male), and 17.6 cm (secondary male). Gonadal maturity stage (GMS) III and IV dominated each observation time. Hence, it was suspected that the fish spawned throughout the year. However, based on the distribution of the GMS, there was an increase in reproductive activity in January-March and July-September, with peak spawning in March and September.